1993
DOI: 10.2136/sssaj1993.03615995005700040011x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Sorption‐Desorption Behavior of Some Acidic Soils of South and Southeast Asia

Abstract: The equilibrium phosphate sorption and release behavior and the kinetics of adsorption were studied in some acidic soils of South and Southeast Asia. Phosphate sorption data at 25 °C were fitted to the Tempkin, Freundlich, and Langmuir adsorption isotherms. The soils varied widely in their capacity to sorh and retain P. During desorption, the amount of sorbed P at a given equilibrium P concentration was always higher than that during sorption, indicating low desorbability of the sorbed P. The kinetic P sorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
30
0
6

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 0 publications
8
30
0
6
Order By: Relevance
“…This is because the Freundlich equation, although originally empirical, implies that the af®nity for sorption decreases exponentially with increasing solution concentration, which is closer to reality. 14,15 Values of n were close to unity in all soils, suggesting partitioning as a dominant adsorption mechanism. Hence, it was possible to compare the K F values and determine the comparative sorption capacities of the soils.…”
Section: Sorption Of Isoxaflutolementioning
confidence: 75%
“…This is because the Freundlich equation, although originally empirical, implies that the af®nity for sorption decreases exponentially with increasing solution concentration, which is closer to reality. 14,15 Values of n were close to unity in all soils, suggesting partitioning as a dominant adsorption mechanism. Hence, it was possible to compare the K F values and determine the comparative sorption capacities of the soils.…”
Section: Sorption Of Isoxaflutolementioning
confidence: 75%
“…Organic matter has been shown to reduce P sorption to soils by competing with P for sorption sites as well as complexing with metal oxyhydroxides (Bhatti, Comerford, and Johnston 1998;Ohno and Crannell 1996;Ohno and Erich 1997;Singh and Jones 1976;Violante, Colombo, and Buondonno 1991). On the other hand, studies have also reported increased P sorption due to the presence of organic matter (Guppy et al 2005a;Harter 1969;Redding, Shatte, and Bell 2006; Sanyal, De Datta, and Chan 1993). Possible mechanisms include the attachment of P to DOM through metal-chelate linkages (Guppy et al 2005a;Zhou, Rhue, and Harris 1997) or inhibiting metal oxide crystallization (Borggaard et al 1990).…”
Section: Phosphorus Sorption From Manurementioning
confidence: 99%
“…However, OM accumulation can potentially contribute to the clogging of pore space, thus decreasing the wetland purification potential. The relationship between P sorption and organic matter content can vary, with some studies reporting a negative correlation [27,43] and others a positive correlation [44]. In the Sadowa wetland, the correlation between OM content and P accumulation in the bed substrate was weak.…”
Section: Discussionmentioning
confidence: 97%